Autonomie, responsabilité et coopération : ce qu'en disent les élèves utilisant un plan de travail - Sylvain Connac
The educational tool « work plan », introduced by Helen Parkhurst at the beginning of the twentieth century, is a document in which each student can find learning activities within his or her reach. It allows the teacher to take into account the diversity of his or her students. If the teacher is constantly being sollicited by different problems, he or she feels quickly overwhelmed and is tempted to return to a traditional pedagogy, which is easier to manage. This research was interested in the opinions of Cycle III primary school students who practise daily work plans. They were questioned via a questionnaire administered by their teacher. More than a thousand French students were able to give their opinions on the nature of autonomy, cooperation between peers and responsible attitudes which a work plan develops.